A survey of North American shelter practices relating to feline upper respiratory management. Issue 4 (April 2013) - Spindel, Miranda E; Slater, Margaret R; Boothe, Dawn
An internet-based survey was conducted to determine common strategies for control of feline upper respiratory infections (URI) in animal shelters. Two hundred and fifty-eight North American shelters responded, representing a spectrum of 57% private non-profit, 27% municipal and 16% combined private non-profit-municipal shelters. All but nine shelters reported having a regular relationship with a veterinarian, 53% had full-time veterinarians and 62% indicated full-time (non-veterinarian) medical staff. However, in 35% of facilities, non-medical shelter management staff determined what medication an individual cat could receive, with 5% of facilities making that decision without indicating the involvement of a veterinarian or technician. Ninety-one percent of shelters had an isolation area for clinically ill cats. The most commonly used antimicrobial was doxycycline (52%), followed by amoxicillin/clavulanic acid (33%). Shelters are using a wide range of prevention measures and therapeutics, leaving room for studying URI in different settings to improve understanding of optimal protocols.